Pengaruh Perencanaan Pajak, Leverage dan Ukuran Perusahaan Terhadap Manajemen Laba pada Perusahaan Manufaktur pada Sektor Industri Barang Konsumsi yang Terdaftar di BEI Periode 2020-2024 - Juliyanto, Juliyanto; Ningsih, Sri Setia; Efriadi, Adi Rizfal (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to analyze the effect of tax planning, leverage, and firm size on earnings management in manufacturing companies within the consumer goods sector listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The research employs a quantitative approach using secondary data obtained from the companies annual financial reports. The sampling method used is purposive sampling based on specific criteria, resulting in 40 companies as the research sample. Data analysis is conducted through descriptive statistics, classical assumption tests, and hypothesis testing. The results indicate that firm size has a positive and significant effect on earnings management, while tax planning and leverage have no significant effect on earnings management. Simultaneously, tax planning, leverage, and firm size jointly influence earnings management.